The EEG in acute ischaemic cerebrovascular disease - Bentes, Carla Cristina Paulo Gabriel (2019)
The electroencephalogram (EEG) is a neurophysiological technique with high temporal resolution and sensibility in the evaluation of brain function in real time. Besides this, EEG is the gold standard for the identification of epileptogenesis and ictogenesis biomarkers. Epileptic seizures and Cerebrovascular disease are two of the most frequent neurological disorders imposing important mutual challenges. Furthermore, in recent years, stroke care has evolved remarkably and, facing a new paradigm of acute standard of care (centred on multidisciplinary Stroke Units), epileptic seizures (as stroke complications) deserve to be rethought. The EEG is an essential neurophysiological exam in the evaluation of patients with epileptic seizures, status epilepticus and/or epilepsy, both for diagnosis and classification, as well as for the establishment of a correct treatment or outcome prediction. Furthermore, EEG has been previously used in cerebrovascular disease with different purposes. However, its clinical usefulness in the differential diagnosis of transient neurological symptoms, specifically in the differentiation between a transient ischaemic attack and some epileptic seizures, and also in the diagnosis or prediction of post-stroke seizures or in post-stroke prognosis prediction, remains uncertain. In this work, we aim to use the clinical model of acute ischaemic cerebrovascular disease to study the value of EEG in the differential diagnosis of transient neurological symptoms, in the diagnosis and prediction of post-stroke seizures and epilepsy, as well as to analyse if electroencephalographic abnormalities and/or epileptic seizures are independent predictors of an anterior circulation ischaemic stroke outcome. Furthermore, since the gold standard of acute stroke care (namely intravenous alteplase treatment) is associated with a reduction of mortality and incapacity of treated patients with possible consequences in post-stroke seizure frequency, but a pro-convulsive and an epileptogenic effect of alteplase has also been described, we aim to test the hypothesis that ischaemic stroke patients treated with intravenous alteplase have a different frequency of epileptic (clinic and/or electroencephalographic) manifestations compared to non-treated patients. Different research methodologies were used in this thesis. A systematic review and meta-analysis of observational studies was performed to evaluate both the frequency of post-stroke (ictal and interictal) epileptiform activity in the EEG, and the quality of studies about this subject. Furthermore, different types of observational studies (including clinical case report, case series and cohort studies) were completed to answer relevant clinical questions. We performed a prospective longitudinal study of possible transient ischaemic attacks (TIA) patients evaluated at a tertiary centre during 36 months, with 1-3 months follow-up and also of acute anterior circulation ischaemic stroke patients, consecutively admitted to a Stroke Unit over 24 months and followed-up for one year. In both studies, patients underwent standardized clinical, diagnostic and neurophysiological assessment. A short duration (≤60 minutes) video-EEG protocol with an extended montage including 64 EEG, two electrooculogram, one electrocardiogram and at least one electromyogram channel was established. Different electroencephalographic investigation technics including visual, back-average and quantitative analysis were used in the clinical workup of patients with possible and definite, transient and established, cerebrovascular disease as tools for the differential diagnosis and for brain functional assessment, concerning not only epileptic manifestations detection and prediction but also to search for predictors of ischaemic stroke functional outcome and vital prognosis. Although epileptic seizures were the most frequent defined final diagnosis (n=13; 16.3%) in our series of 80 patients with difficult-to-diagnose transient neurological symptoms, visual inspection of EEG supported this diagnosis only in 7.5% (n=6) of patients with possible TIA. Moreover, the majority (n=6; 53.8%) of patients with the final diagnosis of epileptic seizures did not have interictal epileptiform activity in an early EEG. Furthermore, early focal slow wave activity, the most frequent EEG abnormality in this patient’s series, did not distinguished between TIA and seizure patients. Our systematic review and random-effects meta-analysis showed that the pooled frequency of post-stroke ictal and interictal epileptiform activity was 7% (95%CI: 3%-12%) and 8% (95%CI: 4%-13%) respectively. Only 2 out of 17 included studies (11.7%) attained the maximum quality score. Moreover, no study exclusively enrolled ischaemic stroke patients, highlighting the need for higher quality studies in the evaluation of epileptiform activity frequency in this type of cerebrovascular disease. Furthermore, due to detection bias, it was not possible to correlate clinical and electrographic seizures. In our prospective cohort of 151 anterior circulation acute stroke patients, we identified different post-stroke, clinical and electroencephalographic, epileptic manifestations including 22.7% (5/22) of acute symptomatic seizures that were exclusively electrographic and therefore could not otherwise be recognised. Furthermore, only EEG back-average analysis allowed the diagnosis of cortical myoclonus during intravenous alteplase perfusion in one clinical vignette included in this work and the recognition of epilepsia partialis continua as a chronic complication of this stroke type in 1.7% of patients. This original work also showed that studied clinical and EEG epileptic manifestations were not significantly different between intravenous alteplase treated and non-treated patients. This thesis work established which abnormalities of an early EEG after acute stroke (background activity asymmetry and the presence of interictal epileptiform activity) are independent predictors of epilepsy in the year after (even when adjusted for clinical and imaging stroke severity). Besides this, early (within the first 72h) post-stroke EEG features, extracted from visual (background activity diffuse slowing and asymmetry) and quantitative (such as delta-theta to alpha-beta ratio and alfa relative power) analysis were recognized as independent predictors of death or functional dependency, at hospital discharge and at 12 months after stroke. Furthermore, outcome models that incorporate delta-theta to alpha-beta ratio or alpha relative power were better than models based exclusively on clinical and imaging-related ischaemic stroke severity at hospital admission. Additionally, post-stroke acute symptomatic seizures and epilepsy were independently associated to death and to an unfavourable outcome 1 year after an acute anterior circulation ischaemic stroke, respectively. Globally, these research projects have shown the value of EEG in the current paradigm of stroke patient’s care. Furthermore, they expand the knowledge both about the EEG role as a complementary neurophysiological tool in general Neurology and about different aspects of the diagnosis and outcome of two of the most prevalent neurological disorders, Cerebrovascular Diseases and Epilepsy, in particular. Beyond the value of specific results, with this work several other research questions about EEG and seizures in ischaemic cerebrovascular disease emerge. Therefore, new possibilities of future research, ideally multicentric, clinical or translational arise.